2016
DOI: 10.1017/pasa.2016.33
|View full text |Cite
|
Sign up to set email alerts
|

Local Stellar Kinematics from RAVE data—VII. Metallicity Gradients from Red Clump Stars

Abstract: We investigate the Milky Way Galaxy’s radial and vertical metallicity gradients using a sample of 47 406 red clump stars from the RAdial Velocity Experiment Data Release 4. Distances are calculated by adopting Ks-band absolute magnitude as −1.54±0.04 mag for the sample. The metallicity gradients are calculated with their current orbital positions (Rgc and Z) and with their orbital properties (Rm and zmax): d[Fe/H]/dRgc = −0.047±0.003 dex kpc−1 for |Z| ≤ 0.5 kpc and d[Fe/H]/dRm = −0.025±0.002 dex kpc−1 for zmax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…had shown that the modes of the intrinsic (dereddened) colours and absolute magnitudes of such a sample are completely defined by the clump giants 1 . The intrinsic colours and absolute magnitudes of the clump vary only with age and metallic-★ E-mail: georgegontcharov@yahoo.com 1 To obtain the modes, we follow , who rounds the observables up to 0.01 mag and finds the tops of their histograms in each ity and can be presented in the space under consideration as some simple functions of | | (Girardi 2016;Önal Taş et al 2016). Therefore, we assumed for our sample that the spatial variations of the modes of the observables BP − RP , RP − 3, G BP + G BP , G RP + G RP , and W3 + W3 reflect the spatial variations of the reddenings ( BP − RP ) and ( RP − 3), extinctions G BP , G RP , and W3 in a combination with some linear gradients of the dereddened colours ( BP − RP ) 0 and ( RP − 3) 0 and absolute magnitudes G BP , G RP , and W3 with | |.…”
Section: Introductionmentioning
confidence: 99%
“…had shown that the modes of the intrinsic (dereddened) colours and absolute magnitudes of such a sample are completely defined by the clump giants 1 . The intrinsic colours and absolute magnitudes of the clump vary only with age and metallic-★ E-mail: georgegontcharov@yahoo.com 1 To obtain the modes, we follow , who rounds the observables up to 0.01 mag and finds the tops of their histograms in each ity and can be presented in the space under consideration as some simple functions of | | (Girardi 2016;Önal Taş et al 2016). Therefore, we assumed for our sample that the spatial variations of the modes of the observables BP − RP , RP − 3, G BP + G BP , G RP + G RP , and W3 + W3 reflect the spatial variations of the reddenings ( BP − RP ) and ( RP − 3), extinctions G BP , G RP , and W3 in a combination with some linear gradients of the dereddened colours ( BP − RP ) 0 and ( RP − 3) 0 and absolute magnitudes G BP , G RP , and W3 with | |.…”
Section: Introductionmentioning
confidence: 99%